Nanostructured kesterite (Cu2ZnSnS4) for applications in thermoelectric devices. (September 2019) - Isotta, E.; Pugno, N. M.; Scardi, P.
Abstract : Kesterite (Cu2 ZnSnS4, CZTS) powders were produced by reactive high-energy milling, starting from stoichiometric mixtures of the elemental components. CZTS forms fine crystals with a cubic structure, which evolves to the stable tetragonal form after thermal treatment. Tablets were produced by cold pressing of the ball milled powder, and sintered up to 660 °C. Seebeck coefficient, electrical resistivity, and thermal diffusivity were measured on the sintered tablets, pointing out the positive effect of CZTS nanostructure and of the rather large fraction of porosity: thermal conductivity is rather low (from 0.8 W/(m K) at 20 °C to 0.42 W/(m K) at 500 °C), while electrical conduction is not seriously hindered (electrical resistivity from 8500 µΩ m at 40 °C to 2000 µΩ m at 400 °C). Preliminary results of thermoelectric behavior are promising.